Evaluation of Dimensional Characteristics of Conductive Pattern Elements of 3D-Printed Circuit Boards - O. N. Smirnova; A. A. Aleksandrov; Yu. S. Bobrova; K. M. Moiseev (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. A review of foreign publications on 3D printing methods shows the possibility of their application for the manufacture of printed circuit boards (PCBs), while demonstrating the growth of interest in this field. One of the available methods is fused deposition modeling, which can be used to form substrates with channels for traces. At present, the minimum channel width comprises 100 µm, which corresponds to the 5th class of PCB accuracy. However, there is no data on how to obtain such dimensions or on the magnitude of their deviation from the given nominal values.Aim. To determine the influence of such factors as nozzle diameter and the number of contours on the dimensional characteristics of PCBs (linear dimensions; trace channel width; trace spacing; via diameters).Materials and methods. To obtain linear models, a full factorial experiment was carried out. The influence of the following materials was evaluated – polylactide (PLA), acrylonitrile butadiene styrene (ABS) and glass-filled ABS; slicers – Ultimaker Cura and PrusaSlicer; 3D printers – Picaso 3D Designer Classic 2016 and Hercules Strong 2017; brass nozzle with diameters ∅0.2 and ∅0.4 mm. The possibility of using brass nozzles coated with chemical nickel for printing with glass-filled filaments was considered. The study was conducted using the facilities of the "Center for Additive Technologies" of Bauman Moscow State Technical University.Results. The possibility of manufacturing PCBs up to the 2nd and 3rd accuracy classes using nozzles with a diameter of ∅0.4 and ∅0.2 mm, respectively, was shown. It was found that galvanic deposition of chemical nickel on a ∅0.2 mm brass nozzle makes it possible to increase the PCB wearability when printing with glass-filled filaments. Recommendations are proposed for selecting an optimal combination of nozzle diameter and the number of contours.Conclusion. The conducted analysis of mathematical models shows the significance of such parameters as nozzle diameter and the number of contours. The results can be used when creating new PCB layouts